Pengaruh Kualitas Pelaporan Keuangan, Modal Sosial, dan Manajemen Kas terhadap Pertumbuhan Pendapatan UMKM - Wilson Candra Teguh Pratama; Retno Pangestu Pangestu (Jurnal Bisnis dan Kewirausahaan, 2024)
SMEs play a vital role as drivers of the national economy and make significant contributions to the Gross Domestic Product (GDP). However, many SMEs face challenges in increasing revenue, primarily due to non-transparent financial reporting, weak social capital, and inefficient cash management. This study aims to analyze the influence of financial reporting quality, social capital, and cash management on the revenue growth of SMEs. The research method employed a survey, collecting data from 200 SMEs using a questionnaire. Data analysis was performed using SPSS to test the hypotheses through multiple regression analysis. The results indicate that all three variables significantly affect revenue growth, with cash management having the most substantial impact. These findings highlight the importance of integrating good financial management practices and strengthening social networks to support revenue growth for SMEs. Therefore, SMEs are advised to enhance financial reporting quality, strengthen social capital, and implement effective cash management as strategies for achieving sustainable growth. This study contributes to the literature and managerial practices in the development of SMEs in Indonesia.